Influencia del tipo de suelo sobre el crecimiento diamétrico anual de juglans neotropica diels y eriotheca ruizii (k. schum.) a. robyns en los sectores del parque universitario Francisco Vivar Castro y la reserva el chilco, al sur de Ecuador - Ruiz Ortiz, Carlos Honorio (2021)
Soil is a determinant factor in the conditions of each site that affects the dymanic of growth of forest species, since it provides all the nutritional requirements to trees. This study aimed to determine how physical and chemical characteristics of soil influence on the growth of "Juglans netropica Diels in the "Parque Universitario Francisco Vivar Castro" sector and Eriotheca ruizzi (K.Schum) A.Robyns in the "El Chilco" reserve. It was carried out a soil analysis for each sector and established the annual diametric growth for each specie; physiographic and dasometric variables were considered. In the analysis of soil, trees were selected from where composite samples were collected to two depths for its subsequent analysis in a laboratory; for determining the growth, core and slices of wood were obtained in order to be analyzed by using LintabTM6 ring measuring system and the Tsap Win program in the Dendrochronology laboratory. For the interpretation and graphic representation of data in the analysis of soil, double- entry tables were used in order to make comparisons between sites and trees. To determine the influence of soil on growth, it was carried out the data analysis by using the Restudio statistical program, in which the analysis of main components was developed. The gathered information through results allowed to establish that the growth of Eriotheca ruizzi (K. Schum) A. Robyns trees are related to the dominance and slope of the tree, whereas high calcium and magnesium contents did not facilitate to its growth. With respect to the Juglans neotropica Diel trees, the growth is very related to coverage, diameter and content of magnesium, while loam soils are limiting factors with a light percentage that reached to the soil. At the end of the research, it is necessary to continue with similar studies to other forest species in similar and different ecosystems that allow to determine requirements of each one and factors which are contributing or limiting growth of forest species. Key words: coverage, dendrochronology, dominance, growth dynamic, soil, physiographic and dasometric variables.